PENERAPAN STRATEGI COOPERATIVE LEARNING MELALUI LAYANAN INFORMASI UNTUK MENINGKATKAN ETIKA PERGAULAN SISWA - Erlina Sari (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2017)
This study aims to improve student learning outcomes about social ethics through the application of cooperative learning strategies. The research method used was classroom action research. The research subjects of class VIII-5 MTs Negeri 2 Medan were 40 people. The instrument used was a test. Data collection techniques are observation, documentation, and interviews. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results showed that: 1) Student ethics in student relations before being provided with information services using cooperative learning strategies respectively low. This can be seen from the lack of student participation to express their opinions when the learning process takes place. 2) The implementation of the service action researchers do as much as 2 cycles, where each cycle consists of 4 stages, namely: (a) planning; (b) implementation; (3) observation; (4) reflection. In the first cycle the researchers only applied the cooperative learning strategy with small group discussion methods. In the second cycle the researchers used the small group discussion method. 3) An increase in students' ethics in relationships is better by using cooperative learning strategies.Keywords: Cooperative Learning, Information Services, Student Social Ethics